A comprehensive metabolomics analysis of Torreya grandis nuts with the effective de-astringent treatment during the postharvest ripening stage. (1st January 2023) - Song, Lili; Meng, Xuecheng; Song, Hanbing; Gao, Lingling; Gao, Yadi; Chen, Wenchao; Huan, Weiwei; Suo, Jinwei; Yu, Weiwu; Hu, Yuanyuan; Yang, Baoru; Zhang, Zuying; et al.
Highlights: The astringency is primarily concentrated in the seed coat rather than the seed kernel. NaHCO3 treatment promotes postharvest de-astringency of Torreya grandis nuts. Differential metabolites analysis showed condensed tannins account for astringency. EGC, GC, catechin, procyanidin (B1-3, C1) are potential components to astringency. Abstract: Astringency removal is important for the quality of Torreya grandis nut and occurs after harvest. Here, we evaluated the effect of NaHCO3 treatment on astringency removal and compared the differential metabolites of the seed coat and kernel using a UHPLC QQQ-MS-based metabolomics approach. The result revealed the nut astringency was primarily enriched in the seed coat with more soluble tannins. The NaHCO3 treatment greatly shortened the de-astringency process, as indicated by a faster conversion of soluble tannins to insoluble tannins and more acetaldehyde production. Besides, a total of 293 metabolites, including 92 phenolic acids and 37 flavonoids, were tentatively characterized in the seed coat. A further comparative analysis of the metabolomics indicated epigallocatechin, gallocatechin, catechin, procyanidin B1, B2, B3 and C1 to be the major metabolites influenced by the NaHCO3 treatment. This study provides new insights regarding the metabolite differences of Torreya grandis nuts processed with different de-astringent treatments.